(untitled) (Research, Society and Development, 2020)
Museums and Science Centers are important spaces for scientific education to the public. School Museums are a special sort of museum that congregates from memory and institutional heritage to pedagogical actions aimed at teaching. The ISERJ Natural History Museum, located at the Instituto Superior de Educação do Rio de Janeiro, is an example of a school museum that has a collection of natural history and pedagogical materials aimed at teaching science. The objective of this work is to verify the role of this school museum in teaching science in general and, consequently, for scientific literacy. Our aim was to analyze the meaning and the impact of a science museum within a formal educational institution, using qualitative research methodology with an emphasis on the historical perspective, through a bibliographic and documentary survey of the museum, from the origin of the collection to its relevance in science education, as well as verifying its meaning today. It was possible to see that the creation of the ISERJ school museum was part of a broader educational policy, which dates back to the end of the 19th century, founded on the premise of a more tangible science education. Despite the little knowledge and use of school museums, their existence can be an excellent opportunity to further highlight their merits and their importance for science teaching.